Geo-cultural space as a basis for the development of the tourist image of the region (Journal of Geography and Environmental Management, 2019)
Geo-cultural space as a basis for the tourist image development of the region. The article examines the concepts ofgeo-cultural space, geographical image and area branding. Due to the basic properties of geo-cultural space, its impacton the image of a given region, the main areas of activity for the branding concept formation of areas can be revealed.Conclusions are made with a focus on Kazakhstan, in consideration of the main issues and trends.